The application of hand-eye coordination test guidelines for table tennis using audio visual media - Dwi Kurniawan, Dennis; Maria Bandi Utama, Alfonsus; Mulyawan, Rizki (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Distance learning in the field of sport education, particularly at the university level, is well suited to independent and structured learning. In the table tennis course, it is necessary to identify the initial ability of PJKR FIK UNY students' hand-eye coordination through the use of audio visual based test guidelines. The method for administering the test is provided during distance learning. This test guideline's application includes experimental research using the pretest-posttest design method. The sample consists of PJKR FIK UNY table tennis students drawn at random from a class of up to 40 students. This study was conducted from February to April 2021. The analysis results of the Paired Sample Test data obtained a value of sig = 0.000 <0.05, the conclusion from the test results is that there is a difference in the effect of hand-eye coordination abilities in table tennis games between before and after being given test guidelines using audio visual media. The conclusion from the application of test guidelines using audio visual media can improve the results of the hand-eye coordination test for PJKR FIK UNY students.